2017
DOI: 10.1088/1361-6641/aa8b03
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Ge-rich Si1−x Ge x (x > 0.9) fin epitaxial layer condensed by dry oxidation

Abstract: We have selectively grown an epitaxial Si 0.35 Ge 0.65 fin layer in a 65 nm oxide trench pattern array and formed a Ge-rich Si 1−x Ge x (x>0.9) fin layer with condensed Ge using dry oxidation. During oxidation of the SiGe fin structure, we found that the compressive strain of the condensed SiGe layer was increased by about 1.3% while Ge was efficiently condensed due to a twodimensional oxidation reaction. In this paper, we discussed in detail the diffusion during the twodimensional condensation reaction as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In our previous study, we reported on the structure of a condensation Si 1−x Ge x fin that can efficiently increase the Ge content to >90% and simultaneously increase the anisotropic in-plane strain by dry oxidation of the Si 0.35 Ge 0.65 epitaxial fin layer. 28) In the oxidation of Si 1−x Ge x , the Si is selectively oxidized, while the Ge is rejected and piled up in a process referred to as Ge condensation. [29][30][31][32][33][34][35][36] The two-dimensional condensation of the Ge in Si 1−x Ge x fins forms a graded Ge content in the bottom of the condensed Si 1−x Ge x film as a result of interdiffusion during condensation; this bottom region acts as a graded strain relaxation buffer (SRB) for the condensed Si 1−x Ge x layer, thus increasing the asymmetric strain.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we reported on the structure of a condensation Si 1−x Ge x fin that can efficiently increase the Ge content to >90% and simultaneously increase the anisotropic in-plane strain by dry oxidation of the Si 0.35 Ge 0.65 epitaxial fin layer. 28) In the oxidation of Si 1−x Ge x , the Si is selectively oxidized, while the Ge is rejected and piled up in a process referred to as Ge condensation. [29][30][31][32][33][34][35][36] The two-dimensional condensation of the Ge in Si 1−x Ge x fins forms a graded Ge content in the bottom of the condensed Si 1−x Ge x film as a result of interdiffusion during condensation; this bottom region acts as a graded strain relaxation buffer (SRB) for the condensed Si 1−x Ge x layer, thus increasing the asymmetric strain.…”
Section: Introductionmentioning
confidence: 99%